Evaluation of Tomato Hybrids for Yield Attributes under Khumaltar Condition - Devkota, S.; Shrestha, S. L.; Dhakal, D. D.; Shakya, S. M.; Pandey, A. (Journal of the Institute of Agriculture and Animal Science, 2018)
An experiment was conducted to evaluate hybrid genotypes of tomato for fruit yield and fruit quality in Horticulture Research Division, NARC, Khumaltar, Lalitpur, Nepal during March to August, 2014 in open field condition. Eleven hybrid genotypes developed from the crosses between HRA and HRD lines, selected as good performer under late blight condition and ‘Srijana’as a local check were taken for the evaluation. Design of experiment was single factorial RCBD with three replications. Observation on traits related to plant morphology, maturity and yield component were recorded to develop, evaluate, identify and recommend high yielding hybrids of tomato. The fruit yield per hectare ranged from 80.83 t/ha (HRA 14 × HRD 7) to 45.89 ton/ha (HRA 15 × HRD 6). Fruit yields of the genotypes HRA 14 × HRD 7, HRA 13 × HRD 7, HRA 20 × HRD 1, HRA 20 × HRD 2, HRA 20 × HRD 6 and HRA 16 × HRD 1 had 80.83 ton/ha, 78.50 ton/ha, 73.75 ton/ha, 70.44 ton/ha, 68.72 ton/ha, 64.64 ton/ha were higher than the yield of ‘Srijana’ (62.33 ton/ha). Based on overall performance, genotypes HRA 14 × HRD 7, HRA 13 × HRD 7, HRA 20 × HRD 1 and HRA 20 × HRD 6 were observed as good performer than Srijana (Check) and selected as high yielder with good fruit quality.